2007
DOI: 10.1002/hep.21703
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and liver injury in hepatitis C is not associated with virus-specific changes in adipocytokines

Abstract: The role of tumor necrosis factor ␣, interleukin 6, leptin, and adiponectin in the pathogenesis of hepatitis C virus (HCV)-associated insulin resistance (IR) remains controversial. We tested the hypothesis that these adipocytokines contribute to chronic HCV-associated IR and liver injury by first comparing their serum levels and homeostasis model assessment of insulin resistance (HOMA-IR) in 154 untreated, non-diabetic, HCV-infected male subjects with fibrosis stage 0-2, to that in 75 healthy volunteers matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
2
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 54 publications
9
100
2
7
Order By: Relevance
“…Serum levels of the adipocytokines leptin and adiponectin were likewise independently associated with IR (adiponectin inversely), but not with HCV infection itself. The authors therefore concluded that these adipocytokines could not account for the increased IR seen in HCV-infected subjects [65] .…”
Section: Inflammation and Irmentioning
confidence: 98%
See 3 more Smart Citations
“…Serum levels of the adipocytokines leptin and adiponectin were likewise independently associated with IR (adiponectin inversely), but not with HCV infection itself. The authors therefore concluded that these adipocytokines could not account for the increased IR seen in HCV-infected subjects [65] .…”
Section: Inflammation and Irmentioning
confidence: 98%
“…Early human studies were conflicting but more recent studies have shown that HCV-induced IR is NOT due to alterations in serum inflammatory cytokines or adipokines [65] . Rather, IR in CHC seems to be due to direct virus-specific effects on insulin signaling.…”
Section: Inflammation and Irmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Cua et al [27] found that insulin resistance and liver injury in HCV are not associated with virus-specific changes in adipocytokines. Nkontchou et al [17] found that IR but not serum leptin levels predicts outcome of viral hepatitis C. In addition, other studies reported that, the structural and nonstructural proteins of HCV may directly cause steatosis by provoking oxidative stress [28,29].…”
Section: Discussionmentioning
confidence: 99%